Social Media and Aqidah Understanding among Generation Z: A Study of Ushuluddin Students at UIN North Sumatra - Arianda Sihombing (Yayasan Salam Cerdas Al-Fattah, 2025)
The background of this research is based on the fact that social media often serves as a space for the dissemination of extreme religious narratives, which has the potential to create misunderstandings of aqidah among Generation Z. The main research question is how social media and aqidah are understood from the perspective of students in the formation of aqidah comprehension. This study employs a descriptive qualitative method involving 2021 cohort students of the Faculty of Ushuluddin and Islamic Studies at UIN North Sumatra who actively use social media. The findings indicate that platforms such as TikTok, YouTube, and Instagram have become effective tools to enhance the understanding of aqidah, connect religious concepts with contemporary issues, and inspire the application of spiritual values in daily life through content delivered by religious figures such as Ustadz Adi Hidayat, Prof. Syahrin Harahap, Ustadz Hanan Attaki, and Ustadz Felix Siau. Nevertheless, a critical attitude is required in filtering information due to the potential presence of distorted content, oversimplification, and provocative narratives.